Electrical Properties of Polymer Electrolytes Membrane and Keratin-PVA as Electrode for Supercapacitors - Hastuti, E.; Rizkia, M. (International Journal of Engineering and Technology, 2019)
Polymer electrolytes membranes were synthesized from Polyvinil Alcohol (PVA) with variations of H3PO4, KI/I2, and H3PO4/KI/I2. Membranes were placed between two electrodes keratin-PVA and pressed at temperature of 50 oC The effect of polymer electrolytesÂ on electrochemical properties of supercapacitors were investigated using LCR meter and charge discharge analysis. Semicircle indicates a movement of charge on electrode surface area and a charge transfer resistance (Rct). Capacitance was increased up to 269 pF after the mixed electrolyteÂ KI/I2- PVA membrane. Spectraâ€™s impedance and permittivity identify polarizability a dielectric material. It is based on the interaction of an external field with the electric dipole moment of the sample and then trapped on the electrode surface. Redox pair I3-/I-Â improves the process ofÂ charging energy and increases capacitance and power density.Â Â